Complicated grief knowledge, attitudes, skills, and training among mental health professionals: A qualitative exploration. Issue 2 (7th February 2022) - Dodd, Anne; Guerin, Suzanne; Delaney, Susan; Dodd, Philip
Abstract: The knowledge, attitudes, skills, and training of professionals regarding complicated grief influence their practice. We conducted 30 semi-structured interviews with psychiatrists, psychologists, and counselor/psychotherapists; the preliminary findings were contextualized via interviews with three experts in complicated grief research/practice. Findings suggest that professionals did not substantially rely on research evidence, favoring instead personal and professional knowledge. They expressed concern regarding the possible pathologization of normal grief that might arise from having a diagnosis of complicated grief. Deficits in professional training were evident. A need for an improved culture of collaboration between researchers and practitioners was identified.